2010
DOI: 10.1387/ijdb.092953hk
|View full text |Cite
|
Sign up to set email alerts
|

Pdx1-transfected adipose tissue-derived stem cells differentiate into insulin-producing cells in vivo and reduce hyperglycemia in diabetic mice

Abstract: Insulin-dependent diabetes mellitus (IDDM) is characterized by the rapid development of potentially severe metabolic abnormalities resulting from insulin deficiency. The transplantation of insulin-producing cells is a promising approach for the treatment of IDDM. The transcription factor pancreatic duodenal homeobox 1 (Pdx1) plays an important role in the differentiation of pancreatic beta cells. In this study, the human Pdx1 gene was transduced and expressed in murine adipose tissue-derived stem cells (ASCs).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
78
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(81 citation statements)
references
References 24 publications
2
78
0
1
Order By: Relevance
“…Transplantation of PDX-1 transduced ADSCs into streptozotocine-induced diabetic mice reduced the blood glucose levels. In this study 25 % of the PDX-1-ADSCs transplanted into pancreas of the streptozotocine treated mice differentiated into insulin-producing cells (Kajiyama et al 2010). …”
Section: Differentiation Of Adipose Derived Stem Cellsmentioning
confidence: 67%
See 1 more Smart Citation
“…Transplantation of PDX-1 transduced ADSCs into streptozotocine-induced diabetic mice reduced the blood glucose levels. In this study 25 % of the PDX-1-ADSCs transplanted into pancreas of the streptozotocine treated mice differentiated into insulin-producing cells (Kajiyama et al 2010). …”
Section: Differentiation Of Adipose Derived Stem Cellsmentioning
confidence: 67%
“…Similar three-step differentiation protocol was able to differentiate the human adipose tissue-derived stem cells into IPCs (Chandra et al 2011). Kajiyama et al (2010) reported that PDX-1 transfected adipose tissue-derived stem cell can differentiate into insulin-producing cells. The human PDX-1 gene was integrated with retrovirus and transducted into ADSCs.…”
Section: Differentiation Of Adipose Derived Stem Cellsmentioning
confidence: 89%
“…ADSCs were immunotyped and then further differentiated into IPCs for transplantation. An ongoing study (49) conducted an in vitro differentiation procedure to generate IPCs by transducing the transcription factor Pdx1, which is important for pancreatic b-cell differentiation. The researchers reported significantly decreased blood glucose levels and increased survival after tail vein injection of Pdx1-transduced ADSCs [immunotyping: paired box 6 (Pax6), Nk2 homeobox 2], wherein they expressed insulin and C-peptide.…”
Section: Therapeutic Effectsmentioning
confidence: 99%
“…Pdx1 cDNA was obtained as previously described [15]. The open reading frame of the human Pdx1 gene was integrated into the retrovirus vector pMSCV-puro.…”
Section: Retroviral Preparationmentioning
confidence: 99%
“…PDX-1-deficient mice die rapidly after birth due to pancreatic insufficiency [14]. Previously, our research group demonstrated that Pdx1-transfected ADSCs can mature in vivo [15]. The combined expression of Pdx1 and MafA with either Ngn3 or NeuroD are required for both exocrine cell reprogramming and staging differentiation [16].…”
Section: Introductionmentioning
confidence: 99%